2016
DOI: 10.4108/eai.20-6-2016.151519
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different signal propagation models for a mixed indoor-outdoor scenario using empirical data

Abstract: In this paper, we are choosing a suitable indoor-outdoor propagation model out of the existing models by considering path loss and distance as parameters. A path loss is calculated empirically by placing emitter nodes inside a building. A receiver placed outdoors is represented by a Quadrocopter (QC) that receives beacon messages from indoor nodes. As per our analysis, the International Telecommunication Union (ITU) model, Stanford University Interim (SUI) model, COST-231 Hata model, Green-Obaidat model, Free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…RMSPE improvements due to recalibration emerged as 0.8% at 900MHz and about 7% at 2GHz; as against 16% at 2.5GHz and close to 60% at 3.5GHz. These metrics are reflected by the predicted pathloss profiles of Figure 7, as well as Figures (8) and ( 9) for the histogram and normal probability plots, respectively. 7.…”
Section:   mentioning
confidence: 81%
See 2 more Smart Citations
“…RMSPE improvements due to recalibration emerged as 0.8% at 900MHz and about 7% at 2GHz; as against 16% at 2.5GHz and close to 60% at 3.5GHz. These metrics are reflected by the predicted pathloss profiles of Figure 7, as well as Figures (8) and ( 9) for the histogram and normal probability plots, respectively. 7.…”
Section:   mentioning
confidence: 81%
“…[7], based on the outcomes of a dedicated measurement campaign, suggested that the performances of the various multi-wall models should significantly improve if reflection effects are accurately taken into consideration. As implicitly suggested by [7], the multi-wall model is also applicable for modelling of indoor-to-outdoor pathloss; and the outcome of investigations by [8] clearly supp.ort that suggestion.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, FSPL losses are usually summed to calculate path losses [ 15 ]. Equation (7) describes the losses in free space, where the frequency ( f ) is expressed in MHz and the distance from the receiving antenna to the transmitting antenna d is given in kilometers [ 59 ]: …”
Section: Technical Analysismentioning
confidence: 99%
“…The path loss exponent h is generally set within ½1:6, 1:8 under LOS or ½4, 6 under NLOS; d ij is the Euclidean distance between the ith grid and information source (lost person) at the jth cycle, d 0 = 1 m is a reference distance for Bluetooth, and s a is the Gaussian random noise. 36 In order to better depict the attenuation of RSSI value during radio signal propagation, the NM is introduced. Thus, the correlation between EM and SSM becomes…”
Section: Definitionmentioning
confidence: 99%